Combined Experimental and Theoretical Investigations on Structural, Spectroscopic, Electronic, and Nonlinear Optical Behaviour of N′-[(E)-(2, 5-dimethoxyphenyl) methylidene]biphenyl-4-carbohydrazide Crystal. (9th July 2021) - Kohli, Navneeta; Jayarama, A.; Kamath, Laxminarayana; Kumar, Anuj
Abstract : The novel Schiff base hydrazones have exciting biological and nonlinear optical (NLO) applications. In our present work, a novel Schiff base hydrazone compound: N′-[(E)-(2, 5-dimethoxyphenyl) methylidene] biphenyl-4-carbohydrazide(DMBC) was synthesized and subjected to FTIR characterization. Quantum chemical calculations were used to further interpret the observed FTIR spectrum quantitatively using potential energy distribution (PED). The geometry of DMBC was optimized using the density functional theory (DFT) approach with the help of the Gaussian 09 W package. Molecular electrostatic potential (MEP) surface and HOMO-LUMO studies were used for the understanding of chemical reactivity sites and the calculation of global reactivity parameters. Intra- and intermolecular interactions within the molecule and crystal packing respectively were examined by NBO and Hirschfeld surface analysis. Nonlinear optical response, which depends upon the delocalization of the π -electrons and intramolecular charge transfer (ICT), was evaluated by dipole moment μ, the polarizability α, and first-order hyperpolarizability β calculations. Hyper polarizability of DMBC molecule is calculated to be 8.0280253 × 10 −30 esu which is 21 times greater than the value of urea. Therefore, synthesized DMBC molecule showed the potential for its use in NLO applications.